PENERAPAN METODE OUTING CLASS DAN HYPNOTEACHING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV SEKOLAH DASAR - Sri Wahyuni; Mira Yanti Lubis; Sutan Botung Hasibuan (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2025)
The purpose of this research is to find out: (1) How students' writing abilities were before using the outing class and hypnoteaching methods in class IV of SD Negeri 0805 Tanjung Baru. (2) How are students' writing abilities after using the outing class and hypnoteaching methods in class IV of SD Negeri 0805 Tanjung Baru. This research uses classroom action research (PTK) consisting of Cycle I and Cycle II. Each cycle consists of planning, implementation, observation and reflection stages. The data collection techniques used are observation, documentation and tests. The subjects of this research were students in class IV of SD Negeri 0805 Tanjung Baru with a total of 30 students (12 boys and 18 girls). Meanwhile, the object is to improve students' writing skills using outing class and hypnoteaching methods in Class IV of SD Negeri 0805 Tanjung Baru. Based on the results of the research carried out by the researcher, it can be concluded that: (1) Students' writing skills before using the outing class and hypnoteaching methods in class IV of SD Negeri 0805 Tanjung Baru were still low, namely that out of 30 students in that class only 3 people (10%) were categorized as good, 20 people (66.67%) were in the poor category and 7 people (23.33%) were in the very bad category. And students' writing abilities after using the outing class and hypnoteaching methods in class IV of SD Negeri 0805 Tanjung Baru increased every cycle. This can be seen in the first cycle, there has been an increase but not yet the maximum. Of the 30 students in the class, the scores obtained by only 2 students (6.67%) were in the very good category, 10 people (33.33%) were in the good category, 14 people were in the very good category. (46.67%) in the poor category and 4 people (13.33%) in the very bad category. And in cycle II, of the 30 students, 9 people (30%) were in the very good category, 17 people (56.67%) were in the good category, and 4 people (13.33%) were in the poor category. By applying the outing class and hypnoteaching methods, students have a wider range of objects to observe than in the classroom, and these two methods can encourage and stimulate the expression of students' ideas both orally and in writing. Based on these learning results, the outing class and hypnoteaching methods can improve the writing skills of class IV students at SD Negeri 0805 Tanjung Baru. (2) The results of observations of students' writing abilities in the pre-cycle were 58.66% in the poor category. In the first cycle, it can be seen that the students' writing ability was 67.83% in the poor category. Meanwhile, the results of observation in cycle II of students' writing ability were 81.16% in the good category. The results of data analysis show that through the application of outing class and hypnoteaching methods, students' writing skills can be improved. The outing class and hypnoteaching methods require students to have a wider range of objects to observe than in the classroom, and these two methods can encourage and stimulate the expression of students' ideas both orally and in writing.